Relationships between principals’ creativity competencies, collaborative school practices, school climate and parental involvement in Malaysian secondary schools - Arivayagan, Keetanjaly (2021)
Despite the increment of school-community relations in Malaysian schools, by the same token, previous studies have pointed out parental involvement in school activities across the country particularly in secondary schools has yet to reach satisfactory and must be improved. Therefore, this study aimed to examine the factors (i.e., principals’ creativity competencies, collaborative school practices and school climate) that influence parental involvement from the stance of teachers in Malaysian secondary schools. This study theorised System Theory as the primary underpinning theory, supported by Overlapping Sphere Theory along with the integration of Generativity Theory, Six Types of Involvement Framework, and Ecological Theory to describe the factors that contribute towards parental involvement in Malaysian secondary schools. The proposed model was empirically evaluated using a postage survey involving 373 respondents, who were randomly selected from four different states: namely Perak, Selangor, Pahang, and Johor. Structural Equation Modelling (SEM) was employed to assess the structural model of the study. All the tested hypotheses were accepted and significant. Findings proposed a model that describes principals’ creativity competencies, collaborative school practices and school climate as significant influences of parental involvement. In precise, the model strengthens the mediation analysis by presenting collaborative school practices that mediated the correlation between principals’ creativity competencies and parental involvement. This study has provided a conceptual theoretical framework from educational administration context to develop and test an integrated model that examines how school-based factors influence parental involvement, which in this case, refers to the willingness of the school to foster parental involvement in secondary schools. As a whole, fostering parental involvement exerts significant effects on school organisational development, programmes, and training. These aspects are essential in the school community and management to impart knowledge to schools and parents as well as to improve the effectiveness and performances of the school organisation, which is bound to substantially strengthen the efforts taken by the Ministry of Education (MoE). This model may facilitate school administrators and teachers to better comprehend school-community relationships, as aligned with the SARANA toolkits and Malaysian Education Blueprint (MEB) initiatives in supporting children’s social and academic development. These findings may provide insights into ways to develop a supportive system that facilitates and encourages parental involvement in secondary schools. More broadly, future research can be done by using split sampling approaches by integrating the proposed model to cross-validate the robustness of the empirical study as well as, conducting comparative studies.